CRIMINAL LEGAL PROTECTION OF THE RIGHTS OF CHILDREN: COMPARATIVE AND LEGAL ANALYSIS OF THE CRIMINAL CODE OF THE REPUBLIC OF KAZAKHSTAN AND PROJECT OF ITS NEW EDITION - Sartayeva Наталья Абаевна (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2014)
The article present a comparative legal analysis of criminal law on the protection of children under the Criminal Code of the Republic of Kazakhstan, with the rules of the new draft Criminal Code of the Republic of Kazakhstan.